(3JMaI GdWGdHjf aj JLhjO cJGH QH GdYGdejfs - (3Rcj GdOjf GdTjN efUhQ Hf YjSi Hf ZGRj GdCfUGQj GdeUQj GdSeGfhOjs ((3eMeO Hf CMeO GdCRgQi s)
(3ChdgG (B:s
(3hHYO ajbhd GdYHO GdabjQ GdTgjQ HGdSeGfhOj bO SCdfj HYV GdCUObGA GdCYRI Ydj ef GdCZGhGJ NOGe GdMLQI GdTQjaI s
(3BNQgG (B:s
(3hef bUOg dG jNjH abO bGd JYGdi(B:"(3hEPG SCdc YHGOj Yfj aEfj bQjH CLjH OYhI GdOGY EPG OYGf (B"(3hgh CUOb GdbGFdjf hCcQe GdCcQejf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCRgQjI (B((3bQGAGJ (B1202) s
Keywords: (3GdbQGAGJ hGdJLhjOs